ANALISIS KINERJA KEUANGAN PERBANKAN SYARIAH DENGAN PENDEKATAN ISLAMICITY PERFORMANCE INDEX PADA PERBANKAN SYARIAH DI INDONESIA - Ria Fatmasari; Masiyah Kholmi (Universitas Muhammadiyah Malang, 2018)
This study aims to analyze Islamic financial finance. This paper discusses the measurement of banking performance with Sharia Performance. Quantitative descriptive research that explains how the overall performance of Islamic banking. Another problem that is less than optimal is the distribution of zakat, as Islamic banks that has succeeds in applying sharia principles are considered lacking in the management of zakat funds. The benefits of this research has to assist stakeholders in taught results and evaluation materials.